2009
DOI: 10.1021/jf803365t
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation Performance of Proteins and Traditional Materials for Spray Dried Flavors

Abstract: The objective of this study was to evaluate the potential of selected proteins as alternative materials for flavor encapsulation by spray drying. Two traditional materials (gum acacia and modified starch) and three proteins (sodium caseinate, whey and soy protein isolates) were used at different infeed solid levels; test compounds included (R)-(+)-limonene and three alpha,beta-unsaturated aldehydes ((E)-2-hexenal, (E)-cinnamaldehyde, citral). The primary criteria for performance were flavor retention during dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
80
0
5

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(97 citation statements)
references
References 31 publications
12
80
0
5
Order By: Relevance
“…Soy protein isolate can be used as an encapsulation material due to its interesting physico-chemical properties, in particular gelforming and emulsifying properties (Gu et al 2009;Dong et al 2013;Nesterenko et al 2013). Many works have indicated that relative to sodium caseinate or whey protein, the encapsulated products with soy protein isolate as a wall material exhibit comparable or even better encapsulation efficiency, and higher stability against oxidation (Charve and Reineccius 2009;Rascon et al 2011;Nesterenko et al 2013). Generally, soy protein isolate is not only used as an individual coating material, but also can be mixed with polysaccharides Rusli et al 2006;Nesterenko et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Soy protein isolate can be used as an encapsulation material due to its interesting physico-chemical properties, in particular gelforming and emulsifying properties (Gu et al 2009;Dong et al 2013;Nesterenko et al 2013). Many works have indicated that relative to sodium caseinate or whey protein, the encapsulated products with soy protein isolate as a wall material exhibit comparable or even better encapsulation efficiency, and higher stability against oxidation (Charve and Reineccius 2009;Rascon et al 2011;Nesterenko et al 2013). Generally, soy protein isolate is not only used as an individual coating material, but also can be mixed with polysaccharides Rusli et al 2006;Nesterenko et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Similar values were obtained by Tonon et al (2008) and Ferrari et al (2012) for the spray drying of blackberry and açai juices using maltodextrin with carrier agents. Charve and Reineccius (2009) evaluated the effect of different proteins on the encapsulation of flavours by spray drying using whey protein isolate, and the authors obtained 87% retention of the volatiles.…”
Section: Total Anthocyanin Retentionmentioning
confidence: 99%
“…This is due to a high encapsulation efficiency of some oils extracted (53%). 17 Gum Arabic is one of the most common wall materials used in microencapsulation by spray drying. It has a good ability to absorb volatiles flavour from surrounding and this will make gum arabic a good wall material for flavour encapsulation.…”
Section: Encapsulation Materialsmentioning
confidence: 99%